ANALISIS KEMAMPUAN MENULIS KARYA ILMIAH GURU EKONOMI DI KABUPATEN PASAMAN BARAT - Yulhendri Yulhendri; Jean Elikal Marna; Oknaryana Oknaryana (Jurnal Inovasi Pendidikan Ekonomi (JIPE), 2018)
Constitution Number 14 Year 2005 on Teachers and Lecturers define that teachers have a position as professionals. Professional teachers should be able to ransfer the knowledge to the students and have ability to develop themselves through scientific papers. This study aims to analyze the ability of teachers in writing scientific papers. The population of the research is the economic teacher in Pasaman Barat Regency. Data were collected using questionnaires distributed to 24 samples. The results of the research show that rhe teachers have low experience in writing and publishing of scientific paper. The result shows that the teachers need tutor in writing and in publication, shown by a very high TCR value of 89.17%.